Pembentukan Temporal Association Rules Menggunakan Algoritma Apriori (Studi Kasus:Toko Batik Diyan Solo) - Annisa Mauliani; Sri Hartati; Aina Musdholifah (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2016)
In this study the adding of time aspect on association rules mining result was used. The aspect of time that was used in this study was date of transactions. The information that was resulted from time aspect adding in association rules mining was known as temporal association rules mining.. In this study, Apriori Algorithm was used for the forming of temporal association rules. This result which show Algorithm Apriori and Temporal Association Rules can be used to get more information about Temporal Association Rules. The Result of this examination can be used for decision support for manager. Because the result of Temporal Association Rules have explanation about event. So from the result of Temporal Association Rules can be knowing, the Temporal Association Rules happened at the time of event.In Ramadan Idul Fitri 2013 and Ramadan Idul Fitri 2014 with parameter assess minsup 10%, mintempsup 5, minconf 50%, resulting different Temporal Association Rules. In Ramadan Idul Fitri 2013, no resulting Temporal Association Rules. While is on Ramadan Idul Fitri 2014 resulting Temporal Association Rules with the biggest value of support 14%, that is BLBP à HPCK.